2013
DOI: 10.5194/bg-10-5517-2013
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous, high-resolution observations of particle flux in the oligotrophic ocean

Abstract: Abstract. Observational gaps limit our understanding of particle flux attenuation through the upper mesopelagic because available measurements (sediment traps and radiochemical tracers) have limited temporal resolution, are labor-intensive, and require ship support. Here, we conceptually evaluate an autonomous, optical proxy-based method for high-resolution observations of particle flux. We present four continuous records of particle flux collected with autonomous profiling floats in the western Sargasso Sea a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…Data from Bio-Argo floats have already demonstrated that multiyear, high-resolution, vertically resolved observations can transform the way we understand ocean ecosystems and biogeochemistry [Bishop et al, 2004;Riser and Johnson, 2008;Boss and Behrenfeld, 2010;Johnson et al, 2010;Estapa et al, 2013]. The results presented here provide another example of how a global fleet of Bio-Argo floats could allow us a quantum leap in understanding of the ocean carbon cycle.…”
Section: Autonomous Platforms and The Ocean Carbon Cyclementioning
confidence: 68%
“…Data from Bio-Argo floats have already demonstrated that multiyear, high-resolution, vertically resolved observations can transform the way we understand ocean ecosystems and biogeochemistry [Bishop et al, 2004;Riser and Johnson, 2008;Boss and Behrenfeld, 2010;Johnson et al, 2010;Estapa et al, 2013]. The results presented here provide another example of how a global fleet of Bio-Argo floats could allow us a quantum leap in understanding of the ocean carbon cycle.…”
Section: Autonomous Platforms and The Ocean Carbon Cyclementioning
confidence: 68%
“…Fluxes may change on short timescales, even within days (e.g., Estapa et al, ; Summerhayes et al, ) as seen in studies in the Sargasso Sea, the North Pacific and the Cape Blanc study area as well (Iversen et al, unpublished data). Off Cape Blanc, the event scale of upwelling favorable winds is a few days and the total upper water column may be influenced within one day only (Pradhan et al, ; Postel, ).…”
Section: Discussionmentioning
confidence: 95%
“…• Supporting Information S1 • Figure S1 Lagrangian float behavior (Bishop, 2009;Bishop et al, 2004Bishop et al, , 2016Bishop & Wood, 2009;Estapa et al, 2013Estapa et al, , 2017. All of these techniques require calibration against appropriate samples-either suspended particles in the case of the methods integrating particle stocks (e.g., Cetinić et al, 2012) or carbon flux samples from direct sediment traps (Estapa et al, 2017).…”
Section: 1029/2018gb006098mentioning
confidence: 99%
“…As with geochemical budget estimates, if one assumes that the floats behave in a Lagrangian manner, or that there is little horizontal variability, then the rates of change of these depth‐integrated stocks between consecutive profiles provide estimates of export fluxes (Briggs et al, ; Dall'Olmo & Mork, ) and sinking speeds (Jackson et al, ). Upward facing optical and imaging sensors or optical sediment traps (OSTs) are used to physically trap and detect sinking particles during single profiles, eliminating the need to assume Lagrangian float behavior (Bishop, ; Bishop et al, , ; Bishop & Wood, ; Estapa et al, , ). All of these techniques require calibration against appropriate samples—either suspended particles in the case of the methods integrating particle stocks (e.g., Cetinić et al, ) or carbon flux samples from direct sediment traps (Estapa et al, ).…”
Section: Introductionmentioning
confidence: 99%